Initial Phases of Starvation and Activity of Bacteria at Surfaces - Kjelleberg, Staffan (1983)
The activity of the hydrophilic Vibrio sp. strain DW1 and the hydrophobic Pseudomonas sp. strain S9, which both undergo starvation-induced responses, was examined at nutrient-enriched and nutrient-deficient interfaces. The initial period of response to a starvation regime (“dwarfing” phase) is a sequence of two processes: fragmentation and continuous size reduction of the fragmented cells. This dwarfing phase is also one of intense metabolic activity as supported by O(2) uptake measurements of the endogenous metabolism and the use of inhibitors of the proton flow, the electron transport chain, and membrane-bound ATPase. Hydrophilic bacteria become even smaller at nutrient-deficient surfaces than in the liquid phase upon starvation, and this is reflected in a higher endogenous metabolism exhibited by surface-associated cells compared with those in the liquid phase. On the other hand, hydrophobic bacteria dwarfing at surfaces did not exhibit a greater size reduction and exhibited an endogenous metabolism that was only slightly higher than that of cells in the liquid phase. Bacterial scavenging of surface-localized nutrients is related to the degree of irreversible binding of dwarf and starved bacteria, which in turn may be related to the degree of cell surface hydrophobicity.